Genome-wide depletion of replication initiation events in highly transcribed regions - Martin, Melvenia M.; Ryan, Michael; Kim, RyangGuk; Zakas, Anna L.; Fu, Haiqing; Lin, Chii Mei; Reinhold, William C.; Davis, Sean R.; Bilke, Sven; Liu, Hongfang; Doroshow, James H.; Reimers, Mark A.; et al. (Genome Research, 2011)
This report investigates the mechanisms by which mammalian cells coordinate DNA replication with transcription and chromatin assembly. In yeast, DNA replication initiates within nucleosome-free regions, but studies in mammalian cells have not revealed a similar relationship. Here, we have used genome-wide massively parallel sequencing to map replication initiation events, thereby creating a database of all replication initiation sites within nonrepetitive DNA in two human cell lines. Mining this database revealed that genomic regions transcribed at moderate levels were generally associated with high replication initiation frequency. In genomic regions with high rates of transcription, very few replication initiation events were detected. High-resolution mapping of replication initiation sites showed that replication initiation events were absent from transcription start sites but were highly enriched in adjacent, downstream sequences. Methylation of CpG sequences strongly affected the location of replication initiation events, whereas histone modifications had minimal effects. These observations suggest that high levels of transcription interfere with formation of pre-replication protein complexes. Data presented here identify replication initiation sites throughout the genome, providing a foundation for further analyses of DNA–replication dynamics and cell-cycle progression.
10.1101/gr.124644.111